2015
DOI: 10.32007/jfacmedbagdad.573373
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD69 molecule in Rheumatoid Arthritis Iraqi patients

Abstract: Background: Rheumatoid arthritis (RA) is an autoimmune disease, where the normal joint tissues attacked by body’s immune system, causing their inflammation. Cluster of Differentiation 69 (CD69) is a human transmembrane C-Type lectin protein encoded by the CD69 gene. It’s expression was induced by activation (in vivo and in vitro) of T lymphocytes and Natural Killer (NK) Cells. As CD69 early activation has been implicated in the pathogenesis of some inflammatory diseases, its expression on peripheral blood T-ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…It ranged between (1.9 -2.2) ds/cm, at a rate of (1.9) ds/cm, and this rate is above the permissible limits in the specifications of Iraqi Standard 417 of 2009 and the World Health Organization [10] for drinking water, table (2,3,4,5). It was noted that the EC values increase towards the Al-Rustamiya station and reach its highest value at the Al-Rustamiya project and after the downstream (W2, W3 station).…”
Section: Electrical Conductivity( Ec)mentioning
confidence: 91%
See 3 more Smart Citations
“…It ranged between (1.9 -2.2) ds/cm, at a rate of (1.9) ds/cm, and this rate is above the permissible limits in the specifications of Iraqi Standard 417 of 2009 and the World Health Organization [10] for drinking water, table (2,3,4,5). It was noted that the EC values increase towards the Al-Rustamiya station and reach its highest value at the Al-Rustamiya project and after the downstream (W2, W3 station).…”
Section: Electrical Conductivity( Ec)mentioning
confidence: 91%
“…Evaluation of water quality according to the total hardship, which is a measure of the Ionian concentration content (Mg +2 , Ca +2 ) which is common in water and is expressed as a caco 3 reward. The hardship is important in managing water quality because it determines the validity of the water for many home, industrial and agricultural uses [12] The results of the study showed the high levels of ion Calciaum compared to Al-Magnasum and the collection of stations, as the value of the hardship(622-782) mg/l for the month of April and July, respectively, Table (2,3,4,5) has a natural geological sources from melting limestone and gypsum rocks found in the Diyala River basin. In addition to the contaminated human activities of the river.…”
Section: Total Hardnessmentioning
confidence: 99%
See 2 more Smart Citations